Effect of Convalescent Plasma in Critically Ill Patients With COVID-19: An Observational Study - Kurtz, Pedro; Righy, Cassia; Gadelha, Monica; Bozza, Fernando A.; Bozza, Patricia T.; Gonçalves, Bruno; Bastos, Leonardo S. L.; Vale, Andre M.; Higa, Luiza M.; Castilho, Leda; Monteiro, Fabio L.; Charris, Nestor; et al. (Frontiers in Medicine, 2021)
Background: Convalescent plasma is a potential therapeutic option for critically ill patients with coronavirus disease 19 (COVID-19), yet its efficacy remains to be determined. The aim was to investigate the effects of convalescent plasma (CP) in critically ill patients with COVID-19. Methods: This was a single-center prospective observational study conducted in Rio de Janeiro, Brazil, from March 17th to May 30th, with final follow-up on June 30th. We included 113 laboratory-confirmed COVID-19 patients with respiratory failure. Primary outcomes were time to clinical improvement and survival within 28 days. Secondary outcomes included behavior of biomarkers and viral loads. Kaplan Meier analyses and Cox proportional-hazards regression using propensity score with inverse-probability weighing were performed. Results: 41 patients received CP and 72 received standard of care (SOC). Median age was 61 years (IQR 48-68), disease duration was 10 days (IQR 6-13), and 86% were mechanically ventilated. At least 29 out of 41CP-recipients had baseline IgG titers >= 1:1,080. Clinical improvement within 28 days occurred in 19 (46%) CP-treated patients, as compared to 23 (32%) in the SOC group (adjusted hazard ratio [aHR] 0.91 [0.49-1.69]). There was no significant change in 28-day mortality (CP 49% vs SOC 56%; aHR 0.90 [0.52-1.57]). Biomarker assessment revealed reduced inflammatory activity and increased lymphocyte count after CP. Conclusions: In this study, CP was not associated with clinical improvement or increase in 28-day survival. However, our study may have been underpowered and included patients with high IgG titers and life-threatening disease.